Rancangan Aplikasi Pembelajaran Interaktif Bangun Datar dan Bangun Ruang Berbasis Android untuk Anak Sekolah Dasar - Supriyadi; Susafa’ati (Pusat Riset dan Inovasi Nasional, 2026)
Android applications have become an integral part of the daily lives of mobile phone users, both adults and children. As technology advances, computer applications and smartphone applications become more sophisticated. Currently, there are many smartphone or computer applications that trigger curiosity to search for and even create their own applications, so many people are spoiled by Android applications, from purchasing daily necessities to buying food, everything can be ordered online. With today's technological developments, the business world and academic fields require maximum effort to produce quality students who pursue science and technology. Problems that often occur in teaching and learning tasks in the classroom include teachers who view students only as objects that can only learn from them. In addition to the fact that students must study many subjects, teachers are also not yet accustomed to using information technology to help students learn about geometric shapes and plane shapes. In this study, the author uses the waterfall method to develop a system or software in a structured and systematic manner. The waterfall model provides a sequential or orderly software life cycle approach starting from analysis, design, coding, testing, implementation, and maintenance. Therefore, the author tries to help solve this problem by creating this Android-based learning application system.